Impact of the Extraction Method and Solvent on the Phenolic Compound Content and Antioxidant Potential of the Aerial Part of Ephedra altissima: In vitro and In silico Studies - Houhou, Dalal; Saad, Somia; Menacer, Rafik; Ferroudj, Sana; Zeraib, Azzeddine; Karoune, Samira; Fadlaoui, Haroun; Bendjemana, Katia (Current Analytical Chemistry, 2026)
BackgroundDespite the widespread use of Ephedra altissima plant in traditional Algerian medicine, the biological potential of this species has still not been well explored.ObjectiveThis study, for the first time, focused on determining the effect of extraction methods and solvents on the phenolic content and antioxidant ability of the aerial part of Ephedra altissima.MethodsExtraction was carried out by maceration and Soxhlet using the solvents H2O, Methanol/H2O and Petroleum ether. The chemical profile of E. altissima was determined by a qualitative HPLC/UV–Visible, and the antioxidant potential was evaluated by in vitro and in-silico studies.ResultsThe aqueous extract obtained by maceration exhibited the greatest total phenol content, while the petroleum ether prepared by Soxhlet extraction demonstrated the highest total flavonoid and condensed tannin contents. The HPLC profile showed the presence of a variety of phenolic compounds. The in-vitro assay results indicated good antioxidant potential. Gallic acid and sinapic acid were highlighted as the most potent antioxidants in the Soxhlet hydro-methanolic and petroleum ether extracts, respectively, according to the machine learning model. Molecular docking predicted the possible antioxidant potential of E. altissima phytocompounds by the interaction with human peroxiredoxin 5, and epicatechin was the most effective ligand. Molecular dynamics simulations confirmed the stability of the epicatechin-Prdx5 complex. Multivariate analysis was used to categorize the Ephedra altissima extracts into three groups according to their phenolic compound content and in vitro antioxidant ability.ConclusionOverall, the results of the present study revealed that the choice of solvent and extraction technique directly influence the biomolecule content and bioactivity of Ephedra altissima aerial part extracts.
Keywords: molecular dynamics